Epistemologi Qalbun Salim: Strategi dan Pendekatan Quran Tarbawi Melawan Dehumanisasi Pendidikan - Izuddin, Azmi; Ramadhan, Mochamad (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2025)
This study constructs an alternative epistemological framework based on Qalbun Salim (The Sound Heart) as a Quranic Tarbawi strategy to counter educational dehumanization. Through philosophical analysis of primary Qur'anic sources and classical exegeses (Tafsir Ibn Kathir and Tafsir Al-Azhar), the research reveals that modern education's dehumanization crisis originates from an epistemological failure - the separation of intellectual from spiritual and moral dimensions. The study redefines Qalbun Salim not merely as a spiritual concept, but as an epistemological organ capable of holistic cognition. The sound heart integrates empirical observation, logical reasoning, and spiritual intuition into a unified cognitive process, functioning as the center for comprehensive knowledge. Findings demonstrate that an effective Quranic Tarbawi strategy requires integrating three fundamental processes: tilawah, tazkiyah, and ta'lim. This integration positions heart purification as the epistemological foundation for meaningful, humanizing learning. The research emphasizes the urgent need for educational paradigm reorientation where Qalbun Salim becomes the ultimate goal, necessitating redesigned learning environments that cultivate heart serenity (thuma'ninah) and develop the heart's epistemic capacity. Ultimately, this epistemology of Qalbun Salim presents a crucial response to contemporary education's humanitarian crisis, restoring education as a medium for humanization and guiding students toward complete human perfection.